Una tecnica para obtener la fase icosahedrica en peliculas delgadas multicapas de AICr - Chaverri, D. (1993)
A method used to produce thin films multilayers of AlCr in vacuum system by electron-beam is discribed. The samples with icosahedral phase undergoes in situ annealing when layers of evaporated material condense on hot substrates (approximately 360°C). Diffraction patterns from Transmission Electron Microscopy were used to identify the icosahedral phase. Samples with phase are compared with others grown on substrates at 100°C.